THE REVELATION OF SOIL GENOTOXICITY USING THE PLANT ASSAYS (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
Using the 02 clone of Tradescantia the frequency of emergence of somatic recessive mutations in stamen hair and micronucleus in tetrads was revealed in soils taken from dwelling areas of Metsamor, Aghavnatun, Armavir, Oshakan, Mrgashat and Ajgeshat villages. The investigations of water extract of grey and black soils was revealed, that heterogeneity of genetic changes depends on the types of soils and the research areas.
Keywords: 02 clone of Tradescantia; extract of grey and black soils; micronucleus; somatic recessive mutations